Diagnosis and management of non-CAH 46,XX disorders/differences in sex development - Yavas Abalı, Zehra; Guran, Tulay (Frontiers in Endocrinology, 2024)
Prenatal onset androgen excess leads to abnormal sexual development in 46,XX individuals. This androgen excess can be caused endogenously by the adrenal or gonads, or by exposure to exogenous androgens. The most common cause of 46,XX Disorders/Differences of Sex Development (DSD) is congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency, comprising >90% of 46,XX DSD cases. Deficiencies of 11β-hydroxylase, 3β-hydroxysteroid dehydrogenase, and P450-oxidoreductase (POR) are rare types of CAH resulting 46,XX DSD. In all CAH forms patients have normal ovarian development. The molecular genetic causes of 46,XX DSD besides CAH are uncommon. These etiologies include primary glucocorticoid resistance (PGCR) and aromatase deficiency with normal ovarian development. Additionally, 46,XX gonads can differentiate into testes, causing 46,XX Testicular (T) DSD, or coexistence of ovarian and testicular tissue, defined as 46,XX ovotesticular (OT)-DSD. PGCR is caused by inactivating variants in the NR3C1 resulting in glucocorticoid insensitivity and the signs of mineralocorticoid and androgen excess. Pathogenic variants in the CYP19A1 lead to aromatase deficiency causing androgen excess. Many genes are involved in the mechanisms of gonadal development and genes associated with 46,XX T/OT-DSD include translocations of the SRY; copy number variants in NR2F2, NR0B1, SOX3, SOX9, SOX10, FGF9, and sequence variants in NR5A1, NR2F2, RSPO1, SOX9, WNT2B, WNT4, and WT1. Progress in the cytogenetic and molecular genetic techniques has significantly improved our understanding of the etiology of non-CAH 46,XX DSD. Nonetheless, uncertainities about the gonadal function and gender outcomes may make management of these conditions challenging. This review explores the intricate landscape of diagnosing and managing these conditions, shedding light on the unique aspects that distinguish them from other types of DSD.